Pengaruh Model Pembelajaran Inquiry Training Berbasis Aplikasi Quiziz terhadap Hasil Belajar Siswa di Madrasah Aliyah Negeri 2 Deli Serdang - Abdul Malik Rambe; Elia Putri (LPPM Politeknik Pratama, 2024)
This research is motivated by the problem of low student physics learning outcomes because teachers do not use a variety of learning models correctly so that the learning model becomes passive. The aim of this research is to determine the influence of the Inquiry Training learning model based on the Quiziz application on students' physics learning outcomes. This research is experimental research. According to Sugiono (2016: 72). The average score obtained by both study groups using the Inquiry Training (X_1) learning model ̅= 14.771. The group that used the Question and Answer learning model had a value of (X_2 ) ̅= 10.857. Based on the calculations carried out, the data obtained were normally distributed and homogeneous. Hypothesis testing for experimental data and the control class obtained a value of tcount of 3.599 and ttable of 1.668, meaning tcount > ttable, so the Ha hypothesis is accepted. The conclusion of this research states that there is an influence of Inquiry Training learning based on the Quiziz Application on student learning outcomes in class X at MAN 2 Deli Serdang T.P 2022/2023.